Imaging of Reactive Astrogliosis by Positron Emission Tomography - Harada, Ryuichi; Furumoto, Shozo; Kudo, Yukitsuka; Yanai, Kazuhiko; Villemagne, Victor L.; Okamura, Nobuyuki (Frontiers in Neuroscience, 2022)
Many neurodegenerative diseases are neuropathologically characterized by neuronal loss, gliosis, and the deposition of misfolded proteins such as beta-amyloid (Abeta) plaques and tau tangles in Alzheimer’s disease (AD). In postmortem AD brains, reactive astrocytes and activated microglia are observed surrounding Abeta plaques and tau tangles. These activated glial cells secrete pro-inflammatory cytokines and reactive oxygen species, which may contribute to neurodegeneration. Therefore, in vivo imaging of glial response by positron emission tomography (PET) combined with Abeta and tau PET would provide new insights to better understand the disease process, as well as aid in the differential diagnosis, and monitoring glial response disease-specific therapeutics. There are two promising targets proposed for imaging reactive astrogliosis: monoamine oxidase-B (MAO-B) and imidazolin2 binding site (I2BS), which are predominantly expressed in the mitochondrial membranes of astrocytes and upregulated in various neurodegenerative conditions. PET tracers targeting to these MAO-B and I2BS have been evaluated in humans. [18F]THK-5351, which was originally designed to target tau aggregates in AD, showed high affinity to MAO-B and clearly visualized reactive astrocytes in progressive supranuclear palsy (PSP). However, the lack of selectivity of [18F]THK-5351 binding to both MAO-B and tau, severely limits its clinical utility as a biomarker. Recently, [18F]SMBT-1 was developed as a selective and reversible MAO-B PET tracer derived through the optimization of [18F]THK-5351. In this review, we will summarize the strategy for molecular imaging of reactive astrogliosis and clinical studies using MAO-B and I2BS PET tracers.